Intraoperative and Anesthesia-Related Cardiac Arrest and Its Mortality in Older Patients: A 15-Year Survey in a Tertiary Teaching Hospital - Nunes, Juscimar C. [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Oliveira, Thais S. [UNESP]; Carvalho, Lidia R. de [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Braz, Leandro Gobbo [UNESP] (Public Library Science, 2014)
Background: Little information is known about factors that influence perioperative and anesthesia-related cardiac arrest (CA) in older patients. This study evaluated the incidence, causes and outcome of intraoperative and anesthesia-related CA in older patients in a Brazilian teaching hospital between 1996 and 2010.Methods: During the study, older patients received 18,367 anesthetics. Data collected included patient characteristics, surgical procedures, American Society of Anesthesiologists (ASA) physical status, anesthesia type, medical specialty team and outcome. All CAs were categorized by cause into one of four groups: patient's disease/condition-related, surgery-related, totally anesthesia-related or partially anesthesia-related.Results: All intraoperative CAs and deaths rates are shown per 10,000 anesthetics. There were 100 CAs (54.44; 95% confidence intervals [CI]: 44.68-64.20) and 68 deaths (37.02; 95% CI: 27.56-46.48). The majority of CAs were patient's disease-/condition-related (43.5; 95% CI: 13.44-73.68). There were six anesthesia-related CAs (3.26; 95% CI: 0.65-5.87) -1 totally and 5 partially anesthesia-related, and three deaths, all partially anesthesia-related (1.63; 95% CI: 0.0-3.47). ASA I-II physical status patients presented no anesthesia-related CA. Anesthesia-related CA, absent in the last five years of the study, was due to medication-/airway-related causes. ASA physical status was the most important predictor of CA (odds ratio: 14.52; 95% CI: 4.48-47.08; P<0.001) followed by emergency surgery (odds ratio: 8.07; 95% CI: 5.14-12.68; P<0.001).Conclusions: The study identified high incidence of intraoperative CAs with high mortality in older patients. The large majority of CAs were caused by factors not anesthesia-related. Anesthesia-related CA and mortality rates were 3.26 and 1.63 per 10,000 anesthetics, with no anesthesia-related CA in the last five years of the study. Major predictors of intraoperative CAs were poorer ASA physical status and emergency surgery. All anesthesia-related CAs were medication-related or airway-related, which is important for prevention strategies.